2023
DOI: 10.3389/fped.2023.1147207
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensiveness of online sources for patient education on hereditary hearing impairment

Abstract: IntroductionThe present study aimed at investigating the readability of online sources on hereditary hearing impairment (HHI).MethodsIn August 2022, the search terms “hereditary hearing impairment”, “genetic deafness”, hereditary hearing loss”, and “sensorineural hearing loss of genetic origin” were entered into the Google search engine and educational materials were determined. The first 50 websites were determined for each search. The double hits were removed and websites with only graphics or tables were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our findings here are, to our knowledge, the most comprehensive examination of the readability of patient‐facing information presented on social media within otolaryngology. They add to an existing body of literature that suggests that online and written patient educational materials are written at a reading level that is too high for many patients to comprehend 15,18,30,39,41 . Further, they show that social media, which many presume to be easily understandable and accessible to all patients, is still incomprehensible for many.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Our findings here are, to our knowledge, the most comprehensive examination of the readability of patient‐facing information presented on social media within otolaryngology. They add to an existing body of literature that suggests that online and written patient educational materials are written at a reading level that is too high for many patients to comprehend 15,18,30,39,41 . Further, they show that social media, which many presume to be easily understandable and accessible to all patients, is still incomprehensible for many.…”
Section: Discussionmentioning
confidence: 82%
“…Except for text in images on Facebook and Instagram, all platforms and modalities were written at a more than sixth-grade level, with some, such as captions on Instagram, as high as a 12th-grade level, similar to that in traditional online patient education material. 15,18,[39][40][41] There is little prior research examining the readability of information presented on social media. A recent study by Chen et al examined the readability of articles linked on Twitter with the #PlasticSurgery tag, and found that the mean reading levels for linked journal articles were over 17 on the SMOG scale, while linked articles written for patient education were more easily readable at 13.9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FKGL scores of professional-oriented websites were found to be higher than patient-oriented websites. Furthermore, in our previous study, hereditary hearing loss was researched on this aspect and all analyzed websites required higher reading levels than the sixth grade ( 21 ). In other fields of medicine, similar results are reported regarding readability ( 22 24 ).…”
Section: Discussionmentioning
confidence: 99%